Acute transverse myelitis in childhood: A single centre experience from North India. (May 2016) - Suthar, Renu; Sankhyan, Naveen; Sahu, Jitendra K.; Khandelwal, Niranjan K.; Singhi, Sunit; Singhi, Pratibha
Abstract: Background: Acute transvers myelitis (ATM) is a rare and disabling condition in childhood. There are only few reports of clinical profile, prognosis and predictors of ATM from developing countries. Objective: To study the clinical profile of children with ATM and predictors of its outcome. Method: Retrospective analysis of children <12 years of age diagnosed with ATM over a period of 6 years from a tertiary care institute. Results: Thirty six children (21 boys, median age-7.5 years) were diagnosed with ATM. Weakness was symmetrical at onset in 27 (75%) children with progression over a median of 2 days (IQR 1–5 days). Severe weakness at onset with lower limb power ≤1/5 on MRC scale was present in 27 (75%), a sensory level in 25(69.4%) and bladder dysfunction in 31(86.1%) children. MRI showed longitudinal extensive myelitis (LETM) in 27 (75%) children and the thoracic cord was most commonly affected [18 (50%)]. On a median follow up of 35 months (range IQR 11–57 months); 15 (41.7%) were non ambulatory or required assistance to walk. Severe weakness at onset with power ≤1 on MRC scale, spinal shock, respiratory muscle weakness, mechanical ventilation, greater mean time to diagnosis and treatment was associated with bad outcome. ATM was a monophasic illness in all, except in 3 children; all with neuromyelitis optica spectrum disorder. Progression to multiple sclerosis was not seen in any child in our cohort. Conclusion: In this series of childhood ATM from North India, the disease was severe, monophasic and involved long segments (≥3) of cord in majority. Nearly half the children remain dependent on follow up. Delayed diagnosis and delayed initiation of steroid therapy was associated with poor outcome. Highlights: Acute transverse myelitis is a severe monophasic illness in developing countries. Outcome is guarded with one third children are left with major neurological sequelae. Delayed diagnosis and delayed initiation of steroid therapy was associated with poor outcome. Genetic and ethnic differences might be responsible for lack of progression to MS in our cohort.